2015
DOI: 10.1002/stem.2026
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Induced Regulatory Human/Murine Mesenchymal Stem Cells as Immune Modulators

Abstract: Over the past decade there has been a growing interest in using mesenchymal stem cells (MSCs) as an immune-regulatory agent for prevention and treatment of various immune disorders including graft-versus-host disease (GVHD), transplanted organ rejection, and autoimmune diseases. However, the high diversity in the results from clinical trials using MSCs for such disorders emphasizes the need for MSCs to be "professionalized" ex vivo to a more defined regulatory phenotype before administering to patients. To thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 104 publications
(182 reference statements)
2
29
0
1
Order By: Relevance
“…A trend for greater response was observed in aGVHD grades C and D than in grade B patients-in other words, in patients with more severe disease and higher mortality risk. This finding is consistent with a report that the potent antiinflammatory and immunosuppressive properties of mesenchymal stromal cells are induced by exposure to high levels of specific cytokines [37,38]. Further research may elucidate this hypothesis, which is consistent with our clinical findings of increased rates of OR and overall survival in the presence of more severe aGVHD as defined by risk stratification and aGVHD grade.…”
Section: Discussionsupporting
confidence: 93%
“…A trend for greater response was observed in aGVHD grades C and D than in grade B patients-in other words, in patients with more severe disease and higher mortality risk. This finding is consistent with a report that the potent antiinflammatory and immunosuppressive properties of mesenchymal stromal cells are induced by exposure to high levels of specific cytokines [37,38]. Further research may elucidate this hypothesis, which is consistent with our clinical findings of increased rates of OR and overall survival in the presence of more severe aGVHD as defined by risk stratification and aGVHD grade.…”
Section: Discussionsupporting
confidence: 93%
“…We primed BMSCs in an inflammatory environment with TNFα or IFNγ, or in reduced oxygen tension (hypoxia, 5% O 2 ), which resulted in increased immunomodulatory efficacy in vitro. These results are corroborated by recently published work from Hinden et al in which they primed MSCs with a triple cocktail of IFNγ, TNFα, and kynurenine to better attenuate graft‐versus‐host disease in a mouse model . Importantly, priming with IFNγ has been previously demonstrated to convert MSCs to an antigen presenting cell phenotype, thereby decreasing their immunomodulatory capacity.…”
Section: Discussionsupporting
confidence: 67%
“…MSCs have been proposed as engraftment promoter cells in bone marrow transplantation and as a therapeutic option in solid organ transplantation rejection (35). In an elegant study, Hinden et al reported that kynurenine contributed to the regulatory phenotype of MSCs through the activation of AhR, leading to suppression of IL-6, induction of leukemia inhibitory factor and activation of the EGFR-COX2 pathway, all of which contributed to the inhibition of the Th17 cells (36). Other than highlighting the potential of MSCs as transplant engraftment promoters, these results emphasize the role of kynurenine, a recognized AhR ligand (10,21), in the modulation of immune tolerance to transplants.…”
Section: Ahr Is Expressed In Several Immune Cells Including T Cells Amentioning
confidence: 99%